Structural Preconditions of City Competitiveness. Some Empirical Results for European Cities - Peter Mayerhofer (Austrian Institute of Economic Research (WIFO), 2005)
Driven by growing internationalisation and high unemployment in Europe concerns about competition between regions and cities and it's consequences for economic and social standards are omnipresent. In their strive for "competitiveness" and a high position of their city in an "European City Hierarchy", urban policy makers take a strongly interventionist stance and foster specific patterns of economic activities, which they suppose to be beneficial to growth. Attempts to grow "future industries" (biotechnology, cultural industries, the media) and "clusters" seem nearly ubiquitous. While these interventions are not necessarily misguided, they seem to be based more on some "success stories" than on a sound empirical basis and hence vary little in content. In this paper we try to contribute to a better understanding of the issue by empirical work on a small database for 46 European Cities. After dealing with some conceptual issues on city competitiveness (section 1) and its measurement (section 2), we analyse the evolutions of European cities from the 1980s onwards (section 3). In what follows, we try to identify sectoral and regional components of growth in European cities (section 4), ask for their preconditions in terms of specialisation and diversity (section 5) and finally proceed to the question, to what extent structural characteristics matter for city growth (section 6). Section 7 concludes.
Keywords: 330; Stadt; Stadtentwicklung; Standortwettbewerb; Internationaler Wettbewerb; Schätzung; Europa